2018
DOI: 10.1111/aab.12434
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and humidity on the survival of Monilinia fructicola conidia on stone fruits and inert surfaces

Abstract: The survival of the fungus Monilinia fructicola on fruit and inert surfaces at different temperatures (range: 0–30°C) and relative humidity (RH) (range: 60–100%) was investigated. M. fructicola conidia survived better on fruit than on inert surfaces. The viability reduction rate at 20°C and 60% RH was 1.2 and 5.8 days−1 on fruit and inert surfaces, respectively. Overall, on fruit surfaces, conidia viability was reduced at high temperatures and was longer at higher RH than at lower RH; in contrast, on inert sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…We do not have a clear reason why conidia decrease drastically on untreated surfaces from 2 to 24 hours, but we attributed this effect to plastic and wood surfaces not provided a suitable place to adhered, germinate and infect conidia. Our results agree with Bernat et al (2018) who showed that M. fructicola conidia viability decrease drastically after some hours at 20 and 30 ºC and 60% HR on inert surfaces.…”
Section: Discussionsupporting
confidence: 93%
“…We do not have a clear reason why conidia decrease drastically on untreated surfaces from 2 to 24 hours, but we attributed this effect to plastic and wood surfaces not provided a suitable place to adhered, germinate and infect conidia. Our results agree with Bernat et al (2018) who showed that M. fructicola conidia viability decrease drastically after some hours at 20 and 30 ºC and 60% HR on inert surfaces.…”
Section: Discussionsupporting
confidence: 93%
“…Monilinia laxa is an airborne plant pathogen subjected to different abiotic environmental factors, such as temperature, humidity, wind, and sunlight, that influence brown rot development. Multiple studies have described the importance of temperature and humidity factors for the successful infection in the field [ 4 , 37 ], its influence on the presence of latent infections [ 2 ], or even in postharvest fruit management [ 38 , 39 ]. However, few have taken into account the influence of light cycles, quantity, or quality of light in Monilinia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorine, sodium hypochlorite, peracetic acid, and hydrogen peroxide are the most common aqueous disinfectants used in packing houses to disinfect fruit when it arrives from the field and also to clean the surfaces of bins or facilities. Sodium hypochlorite has shown great disinfecting power on surfaces infected with M. fructicola [ 50 ]. Chlorine at a concentration of 50 mg L −1 significantly decreased conidial germination of Mucor piriformis and Penicillium expansum after 30 s of treatment, although fruit rotting was not controlled.…”
Section: Discussionmentioning
confidence: 99%